THE INFLUENCE OF OVEN SYSTEM SCARIFICATION TO GERMINATION AND EARLY GROWTH SEED TEAK PLANTS (Tectona grandis L.F) - Haryuni FP UTP Ska; Harjanto FP UTP Ska (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta)
ABSTRACT The research of influence oven system scarification to germination and early growth of teak plants (Tectona grandis L.F), the aim of this research to search the effect of temperature and time of ovening for the germination and the growth of teak seed. Research have been executed in Departemen of Agriculture inUTP. 4Mart 2006 up to 15 August 2006. This research used Completely Randomized Design with pattern treatment of single factor consisting of 3 times restating, covering;1. Ovens temperature 20º C during 60,120,180, 240 minutes;2. Ovens temperature 30º C during 60, 120,180, 240 minutes;3. Ovens temperature 40º C during 30, 60, 120, 180, 240 minutes. The result of research concluded as follow is: High of crop, amount of leaf, bar diameter, radiks volume its influence significant different, for the weight of is fresh biomass weight and dry biomass weight is significant different. Best result of the research is B2 at treatment of ovening of temperature 20º C during 120 minutes. High heavy growth 50,83 gr. Obtained of treatment of A1 (ovens temperature 20º C during 120 minutes). While lowest growth of teak seed 25,42 gr from A1 treatment (ovens temperature 20º C during 60 minutes).